KESENIAN BARONGSAI SEBAGAI SARANA PEMBAURAN MASYARAKAT TIONGHOA DI ACEH TAMIANG - madhan anis; Yunita Sari (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2018)
In contrast to ancient times, now not only the Chinese people who play the Lion Dance, but also many indigenous Indonesian people who participated. This can be seen in one form of social interaction between the ethnic Chinese community and the indigenous population, namely the participation of the indigenous ethnic community in the art of lion dance both as a performer and also a spectator who also enlivened the performance of the dance of the lion dance. After the end of the new order period and entering a period of reform, Chinese culture began to develop. One of them is lion dance. Barongsai art began to be known to all regions in Indonesia. This participation is also a cultural assimilation between indigenous ethnic communities and ethnic Chinese communities, as is the case now in Aceh Tamiang District.